THE LOST ART OF PUBLIC READING OF SCRIPTURE - Budianto Lim (STT Amanat Agung, 2015)
Protestant churches are grounded on the conviction of Sola Scriptura. The reality, however, this conviction is presented only through preaching. This article presents a proposal based on biblical foundations that churches need to pay more attention to the art of public reading of Scripture. The writer is convinced that when churches reconsider the way the Bible is read publicly during the Sunday Worship, there will be a renewal of heart in the life of Christians.